Proteolysis of Tissue Factor Pathway Inhibitor (TFPI) by Plasmin: Effect on TFPI Activity - Li, Anguo; Wun, Tze-Chein (Thrombosis and Haemostasis, 1998)
An important regulator of the initiation of blood coagulation is the plasma glycoprotein, tissue factor pathway inhibitor (TFPI). TFPI inhibits factor Xa and factor VIIa/tissue factor complex, thereby dampens the proteolytic cascade of the tissue factor pathway. Plasma clot lysis is primarily mediated by the fibrinolytic enzyme, plasmin, which is generated through limited proteolysis of plasminogen by endogenous or exogenously administered plaminogen activators. In this study, the interaction of plasmin with recombinant E. coli-derived TFPI (rTFPI) was examined. Plasmin was found to cause a time and concentration dependent proteolysis of rTFPI, resulting in the decrease of anti-factor Xa (measured by chromogenic substrate assay) and anticoagulant (measured by tissue factor-induced clotting assay) activities. Amino-terminal sequencing of the proteolytic fragments revealed that plasmin cleaved rTFPI at K86-T87, R107-G108, R199-A200, K249-G250, and K256-R257. Western blot analysis showed that proteolysis of exogenously added rTFPI also occurred in plasma supplemented with urokinase, and this is accompanied by decrease of anticoagulant activity. These changes were abolished by addition of aprotinin, an inhibitor of plasmin. These data indicate that TFPI is susceptible to proteolysis when plasma fibrinolytic system is activated. The results taken together suggest that plasmin degradation of TFPI may contribute to rethrombosis after thrombolysis, and may contribute to the variability of the efficacy of TFPI in various thrombolysis/reocclusion studies reported previously.